KOMPETENSI DOSEN HUBUNGANNYA DENGAN PRAKTEK ORGANISASI PERGURUAN TINGGI SWASTA DI KOPERTIS WILAYAH VI JAWA TENGAH - Prihatin Tiyanto PH (AKSES: Jurnal Ekonomi dan Bisnis, 2010)
The aim of this research are to  understand teacher competence relation with organisation practice in PTS. Responden in this research are profesional teacher this receive sertificate profesional from Dikti with 2008 until 2009. The sum of profesional certificate teacher 441 person, in the 2008 size 228 teacher and 2009 size 213 person. Sample zise 120 teacher all of university in PTS central Java. The tool use are descriptive analysis and SEM with AMOS Program serie 5. The results  will describe below: 1). The teacher competence are not relationship with compesation returns. 2) The teacher competence are not alignment with of performance. 3). The competence teacher are not contribution to organisation strategy. 4). The high level education are not improve the teacher compensation. 5). The high level education this improve the teacher compensation. 6). The experience will be improve the teacher compensation. 7).  The experience will be improve job performance. 8). The experience are not results the teacher competence. 9).  The compensation will be improve the teacher compensation. 10). The compentasion are not give the contribution organisastion strategy. 11). The performance will be improve the contribution strategy.Key Word: Competence, compensation,  experience, education, performance, organisation strategy.